Width determination for deep grooves in dark-field confocal microscopy measurements. (1st December 2022) - Liu, Jian; Jiang, Yong; You, Xiaoyu; Liu, Chenguang
Abstract: Dark-field confocal microscopy is effectively used for 3D surface and subsurface measurement due to its ability to suppress strong reflected signals from measured surfaces. However, in 3D characterization of microstructure morphology, edge imaging degrades due to the influence of microstructure edge occlusion, so the microstructure edge position cannot be accurately determined. This limitation is serious when dark-field confocal microscopy is used for width determination of deep grooves/step samples. In this paper, a method for determining the width for deep grooves in dark-field confocal microscopy is proposed to determine the edge position with the groove's lower surface in focus. Experimental results show the width determination method has higher precision compared to conventional 1/4 edge determination, reducing the standard deviation by 57.58%.